Absorptive routines and international patent performance - Fernando E. García-Mui\~na; Rocío González-Sánchez (BRQ Business Research Quarterly, 2017)
Patents on an international level are essential for firm results. Accordingly, the use of external sources of knowledge acquires crucial importance to get global innovations and create competitive advantages. For that reason, the literature has highlighted the strategic role of the absorptive capacity construct. We enrich the treatment of the absorptive capacity phases including the moderating effects between routines associated to the traditional potential-realized absorptive capacities. Taking into account external knowledge search strategies, the deeper external relationships, the better transference and appropriation of specific external knowledge. Nevertheless, when the moderating role of assimilation is included, cooperation agreements appear as the most efficient source of external knowledge. Finally, we show that technological tools let firms store and structure the information making easier its use for international patenting. This positive effect is reinforced in the presence of exploitation routines, since technological knowledge will better fit to the industry's key factors of success."
Keywords: 650; Absorptive capacity; Knowledge management; Search strategies; International patents